A Scoping Review Exploring Whether a Free “Offer” Devalues or Widens Sport and Physical Activity Participation Amongst Children and Young Adults Aged 0–25? - Durden-Myers, E. J.; Swaithes, L. (Frontiers in Sports and Active Living, 2022)
Background Socio-economic status continues to mediate physical activity engagement, despite a range of interventions aimed at reducing inequalities and widening sport and physical activity participation. As a result there has been increasing interest amongst policy makers, national governing bodies (NGB), county sports partnerships (CPS) and the sport and physical activity sector more broadly, in understanding how best to reduce inequalities and widen participation. The “price point” of offers and whether a “free offer” enables or devalues participation, has been a key area of interest. This scoping review aimed to explore this topic further by investigating whether “a free “offer” devalues or widens sport and physical activity participation amongst children and young adults aged 0-25?”. Methods This scoping review searched three electronic bibliographic databases (MEDLINE, PsycINFO, SPORTDiscus) using a structured search strategy to identify articles published between 2017 and January 2022. Studies were included using the PICO criteria of; Population: children and young adults aged 0-25; Intervention: free “offer” relating to physical activity; Context: areas of deprivation in the UK; Outcome: engagement, involvement, participation in sport and physical activity. Results and Discussion Five studies were eligible after screening 1301 titles and reviewing 14 full-text studies. Features reported included intervention design, outcomes, potential challenges and wider implications / future recommendations. Specifically, a narrative synthesis of the key themes of participation deprivation and cost effectiveness were outlined in more detail. A subsidized cost or free offer can improve participation generally and in attracting those from lower socio-economic backgrounds. However, the impact of such initiatives decrease with increasing deprivation highlighting that groups with the highest levels of deprivation have wider complexities affecting their participation. Competing priorities and potentially unrealistic expectations at stakeholders level was also identified. Conclusion Despite the paucity of current research exploring the impact of a “free offer” in children and young adults, recommendations for future research, practice and policy included the need for longitudinal, more holistic and participant centric approaches. Further research is required to explore the impact of a “free offer” from an individual, societal and policy-level perspective, in widening and increasing participation in sport and physical activity.